Contextual Cueing Accelerated and Enhanced by Monetary Reward: Evidence From Event-Related Brain Potentials - Zhao, Guang; Zhuang, Qian; Ma, Jie; Tu, Shen; Li, Shiyi (Frontiers in Human Neuroscience, 2021)
The vital role of reward in guiding visual attention has been supported by previous literatures. Here we examined the motivational impact of monetary reward feedback stimuli on visual attention selection using an Event-related potential (ERP) component called stimulus preceding negativity (SPN) and a standard contextual cueing paradigm. It has been proposed that SPN reflects affective and motivational processing. We focused on whether incidentally learned context knowledge could be affected by reward. Both behavior and brain data demonstrated that contexts followed by reward feedback not only gave rise to faster implicit learning, but also obtained larger contextual cueing effect (CC).